Alternative adenosine Receptor activation: The netrin-Adora2b link - Yuan, Xiaoyi; Mills, Tingting; Doursout, Marie-Francoise; Evans, Scott E.; Vidal Melo, Marcos F.; Eltzschig, Holger K. (Frontiers in Pharmacology, 2022)
During hypoxia or inflammation, extracellular adenosine levels are elevated. Studies using pharmacologic approaches or genetic animal models pertinent to extracellular adenosine signaling implicate this pathway in attenuating hypoxia-associated inflammation. There are four distinct adenosine receptors. Of these, it is not surprising that the Adora2b adenosine receptor functions as an endogenous feedback loop to control hypoxia-associated inflammation. First, Adora2b activation requires higher adenosine concentrations compared to other adenosine receptors, similar to those achieved during hypoxic inflammation. Second, Adora2b is transcriptionally induced during hypoxia or inflammation by hypoxia-inducible transcription factor HIF1A. Studies seeking an alternative adenosine receptor activation mechanism have linked netrin-1 with Adora2b. Netrin-1 was originally discovered as a neuronal guidance molecule but also functions as an immune-modulatory signaling molecule. Similar to Adora2b, netrin-1 is induced by HIF1A, and has been shown to enhance Adora2b signaling. Studies of acute respiratory distress syndrome (ARDS), intestinal inflammation, myocardial or hepatic ischemia and reperfusion implicate the netrin-Adora2b link in tissue protection. In this review, we will discuss the potential molecular linkage between netrin-1 and Adora2b, and explore studies demonstrating interactions between netrin-1 and Adora2b in attenuating tissue inflammation.